Quality Assurance Institutions in Various Countries in Teacher Education and Suggestions for Turkey - Metin KAYA (Yükseköğretim ve Bilim Dergisi, 2017)
The purpose of this study is to evaluate comparatively the structures of quality assurance systems, methods and techniques, evaluation processes and results of the teacher training programs of some countries. By doing this, some suggestions were made about the quality assurance systems for Turkish teacher training programs. In conclusion, countries developed quality assurance systems to monitor, improve, validate the inputs, process and outputs of their teacher training programs. In Turkey, to better equip the teacher candidates for the future teacher training programs should be updated by taking into consideration the changes in the field. And also some thematic quality assurance systems can be developed for the critical steps such as faculty– school cooperation and pedagogical formation programs.